Representações sociais de formação continuada dos professores de educação física de escolas públicas do estado do Espírito Santo - Loureiro, Walk (2012)
The main objective of the work is to understand the thought, the feeling and the actions taken for the teachers of Physical Education in relation its continued formation. For in such a way it chooses the great theory of the Social Representations, especially had the importance that this theory attributes to the common sense, that is one of the slight knowledge central offices for the concept of social representation. Opting to Boarding Structural, that corresponds to one of the three chains that compose that great theory, raises hypotheses for the existence of the social representation of continued formation, treating to its internal organization and the cognitive dimension of the same one. Research deals with qualitative that if it uses of the Technique of Free Association (and the treatment of the data reached by means of software EVOC 2000) and of the Technique of Choice for Successive Decreasing Graduation - that they are two sufficiently common tools of research in the inquiries on social representations -, allied with the accomplishment of semistructuralized interviews. It points with respect to the occurrence of a phenomenon that has dislocated the central nucleus of the social representation of continued formation of the learning for the qualification becoming the search for qualification in the continued formation an individual attribute, of exclusive responsibility only e of the teachers